Main processes of mechanization of biomass from sugarcane: An approach using agriculture 4.0 - Magalhães, Karen Giovanna Duarte; Soares, Victoria Victor; Lima, Lucas Franklin de; Moura, Luiz Eduardo Freitas de; Melo, Katia Moreira de; Nascimento, José Heriberto Oliveira do (Seven Editora, 2024)
Faced with the great problem of petroleum fuels, it is essential to invest in new clean energy sources. This scenario promotes the search for new raw materials and sustainable routes that can be used alternatively, such as the so-called biomass, materials rich in plant or animal organic matter. In this context, the biomass obtained from sugarcane stands out. It has been used in various ways, from a natural input to obtain sugar and molasses production to an energy source to obtain ethanol, a renewable fuel. Thus, in view of the great potential of sugarcane, the present work consists of a conceptual literature review, addressing the main challenges in its production in Brazil, and exploring Agriculture 4.0. The main results of the study demonstrate that the adoption of Agriculture 4.0 and, consequently, the mechanization of sugarcane harvesting are not only urgent needs, but must also be carefully implemented to bring more benefits to the companies involved in its production. DOI:https://doi.org/10.56238/sevened2024.007-046